Festival 1000 Tumpeng: Komodifikasi Tradisi, Pariwisata, dan ‘Territoriality’di Gunung Kelud - Edlin Dahniar Alfath; Yogi Setya Permana (Masyarakat, Kebudayaan dan Politik, 2016)
This research explains how tradition can be modified for tourism and political purposes. The tradition that will be elaborated in this essay is "Festival 1000 Tumpeng Kelud". This festival adapts tradional Javanese cultural ceremony. The commodification of tradition is associated with the development of tourism in the area of Kelud Mountain, East Java. Furthermore, tourims activity in Kelud Mountain is part of strategy to defend particular territory in a disputed area. This is ethnography research with qualitative data and descriptive analysis, located in Sugihwaras village. Key informants of this research are special figure in society whom considered as person who can communicate with Kelud Mountain, society representative, BMKG officers, and Village officials. This essay concludes that there are three layers purposes of convening "Festival 1000 Tumpeng" initiated by the government of Kediri namely preservation of traditions and gratitude expression to God, tourism promotion, and politics of territoriality related to disputed area with Blitar Regency.